2014
DOI: 10.1248/cpb.c13-00504
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Analysis in a Liposome Suspension Using Lapachol as a Hydrophobic Electro Active Species

Abstract: This study demonstrated that the electro-chemical analysis of hydrophobic quinones can be performed in liposome suspension systems. We prepared and analyzed liposome suspensions containing lapachol, which is a quinone-based anti-tumor activity compound. In this suspension system, a simple one redox couple of lapachol is observed. These results are quite different from those obtained in organic solvents. In addition, the pH dependence of redox behaviors of lapachol could be observed in multilamellar vesicle (ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Many studies on the redox properties of this anthraquinone derivative have been reported. [4][5][6][7][8] Most of these relate to anion radicals and include changes in reduction potential because of intramolecular and intermolecular hydrogen bonds, 5) and disproportionation/comproportionation reactions of reductants and dianions of anthraquinone 7) ; there are no reports on the properties of oxidized radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the redox properties of this anthraquinone derivative have been reported. [4][5][6][7][8] Most of these relate to anion radicals and include changes in reduction potential because of intramolecular and intermolecular hydrogen bonds, 5) and disproportionation/comproportionation reactions of reductants and dianions of anthraquinone 7) ; there are no reports on the properties of oxidized radicals.…”
Section: Introductionmentioning
confidence: 99%